2021
DOI: 10.1039/d1py00334h
|View full text |Cite
|
Sign up to set email alerts
|

Porous hollow TiO2microparticles for photocatalysis: exploiting novel ABC triblock terpolymer templates synthesised in supercritical CO2

Abstract: We report the synthesis of phase separated PMMA-b-PS-b-P4VP microparticles via RAFT-mediated dispersion polymerisation in scCO2 and their use as a structure-directing agent for the fabrication of TiO2 microparticles for photocatalysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 64 publications
0
3
0
Order By: Relevance
“…Block Copolymer composites were synthesised using a two-pot seeded dispersion method in an in-house built scCO 2 autoclave (Scheme 1), similar to methods reported in previous publications. 28,31 Firstly, a 50 kg mol −1 PMMA macro-RAFT agent was synthesised. MMA (10 g, 99.9 mmol), AIBN (16.4 mg, 0.10 mmol), DDMAT (72.8 mg, 0.20 mmol) and PDMS-MA polymeric stabiliser (0.5 g, M n ∼ 10 kg mol −1 ) were mixed in a sealed vial and degassed by purging with argon for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Block Copolymer composites were synthesised using a two-pot seeded dispersion method in an in-house built scCO 2 autoclave (Scheme 1), similar to methods reported in previous publications. 28,31 Firstly, a 50 kg mol −1 PMMA macro-RAFT agent was synthesised. MMA (10 g, 99.9 mmol), AIBN (16.4 mg, 0.10 mmol), DDMAT (72.8 mg, 0.20 mmol) and PDMS-MA polymeric stabiliser (0.5 g, M n ∼ 10 kg mol −1 ) were mixed in a sealed vial and degassed by purging with argon for 30 minutes.…”
Section: Methodsmentioning
confidence: 99%
“…This particular block copolymer has already been successfully used as a structural template for the fabrication of polymer-inorganic composites, owing to the selective coordinative bonding ability of the pyridinyl nitrogen. 27,28 In this approach, the 4VP monomer is combined in scCO 2 with the dissolved silver precursor to allow incorporation of AgNP throughout the formed block copolymer microparticles. The resulting polymer-AgNP composite powders were tested for their biocompatibility and antimicrobial activity over an extended time-period.…”
Section: Introductionmentioning
confidence: 99%
“…Howdle and coworkers reported the use of RAFT dispersion polymerization to generate triblock copolymers (PMMA- b -PSt- b -P4VP) in supercritical CO 2 . 283 TEM images revealed that PMMA- b -PSt diblock copolymers could adopt a lamellar morphology, and that the addition of the P4VP block could lead to the formation of distinct spherical domains in the lamellar sheets through microparticle confinement. This morphology is less pronounced at the particle core due to the increased spherical constraint at the centre of these microstructures.…”
Section: Morphologymentioning
confidence: 99%